A Vitiligo-like Cutaneous Reaction Induced by Ribociclib in Advanced Breast Cancer: An Unusual Case Report from Colombia - John Fernando Montenegro; Giovanna Patricia Rivas-Tafurt; Sinthia Vidal-Cañas; Miguel Ángel Diaz-Diaz; Cesar Eduardo Bermudez; Daniel Florez; Andres Felipe Bravo-Gustin; Yamil Liscano (Diseases)
Background: Cutaneous toxicities associated with CDK4/6 inhibitors are uncommon but may affect treatment adherence. We present the case of a patient with advanced breast cancer who developed vitiligo-like lesions after initiating ribociclib, contributing to the growing evidence of this under-recognized adverse effect. Methods: We present the case of a 72-year-old woman diagnosed in 2007 with early-stage, luminal A, HER2-negative breast cancer, initially treated with surgery and tamoxifen. In 2022, she experienced locoregional recurrence with bone metastases. In January 2023, she began treatment with ribociclib plus letrozole. Two months later, she developed intense pruritus, xerosis, and paresthesia, followed by hypopigmented lesions on her face and upper extremities. Clinical evaluation, supported by photographs and a skin biopsy (led to a diagnosis of ribociclib-induced vitiligo. Management included dose adjustments to the ribociclib and dermatologic treatments, including topical corticosteroids, antihistamines, and short courses of oral prednisone. Results: By September 2024, her skin lesions had stabilized and her pruritus improved with a reduced dose of ribociclib (one tablet per day). However, the hypopigmented patches persisted, mainly on her face and extremities. Despite these cutaneous effects, she maintained an acceptable quality of life and continued effective oncologic treatment. Conclusions: This case highlights the importance of early recognition and management of ribociclib-related cutaneous toxicities. A multidisciplinary approach is essential to minimize adverse effects without compromising therapeutic efficacy. Further research into the dermatologic manifestations of targeted therapies is needed to optimize patient care.